2020
DOI: 10.1002/lt.25870
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Mac‐2 Binding Protein Glycosylation Isomer to Evaluate Graft Status After Liver Transplantation

Abstract: Mac‐2 binding protein glycosylation isomer (M2BPGi) is a novel liver fibrosis biomarker, but there are few studies on M2BPGi in liver transplantation (LT) recipients. This study aimed to evaluate the utility of M2BPGi measurement in LT recipients. We collected the clinicopathological data of 233 patients who underwent a liver biopsy at Kyoto University Hospital after LT between August 2015 and June 2019. The median values of M2BPGi in patients with METAVIR fibrosis stages F0, F1, F2, and ≥F3 were 0.61, 0.76, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Before conducting the clinical study, we assumed the in uence of liver in ammation on M2BPGi levels as previously reported [12]. Kimura et al reported a positive correlation between M2BPGi level and necroin ammatory activity and stated that M2BPGi can be used to assess the degree of liver in ammation in patients with liver diseases [12].…”
Section: Discussionmentioning
confidence: 94%
“…Before conducting the clinical study, we assumed the in uence of liver in ammation on M2BPGi levels as previously reported [12]. Kimura et al reported a positive correlation between M2BPGi level and necroin ammatory activity and stated that M2BPGi can be used to assess the degree of liver in ammation in patients with liver diseases [12].…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, it is possible that only GCDCA was correlated with M2BPGi in this study, because adult patients with biliary atresia with normalized bilirubin levels had only slight bile acid congestion. Recently, M2BPGi has been shown to be sensitive to the degree of liver inflammation 14 . Whether bile acids themselves are correlated with the degree of liver fibrosis or potentially contribute to liver damage remains controversial 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of liver fibrosis is one such important scenario, particularly in the setting of early injury and rejection. Recently, Kimura et al 24 identified Mac-2 binding protein glycosylation isomer as a serological marker of postliver transplant fibrosis and disease activity that closely correlated with liver histology. In the pediatric population, serum levels of tissue inhibitor of matrix metalloproteinase-1 and the AST-to-platelet ratio index have been shown as accurate predictor of allograft fibrosis, serving as complementary tools to invasive biopsy.…”
Section: Clinical Applications Of Biomarkersmentioning
confidence: 99%